PEMBUATAN DISAIN BINGKAI BAMBU KHAS DAERAH SULAWESI SELATAN - Langke, Aminuddin Langke (Universitas Patria Artha, 2022)
. There are as many as 176 species of bamboo in Indonesia out of a total of 1620 bamboo species in the world originating from 80 countries. This means that 10% of the world's bamboo species are in Indonesia. In fact, about 105 types of bamboo in Indonesia are endemic plants. Of the bamboo grown in Indonesia, 50% is endemic bamboo and half of that amount has been utilized by the community.Therefore, the Government considers that bamboo is very important to be developed towards a people's economy with a touch of technology so that the added value of bamboo is better. Bamboo is beneficial for the economy, conservation, and culture. Indonesia is estimated to have more than 1 million hectares of bamboo plants. However, only 25,000 hectares have been managed in the form of forest/bamboo gardens, while the rest is growing sporadically. In Indonesia, bamboo has very promising potential to be put to good use. This plant is also easy to develop and has a relatively fast life cycle with a harvest time of only 3-4 years.Therefore, in order to present a training activity as an embodiment of the preservation of development activities (fine arts), work activities are designed a) Calligraphy sketches/paintings (Lontara Script Art) b) Sketches/paintings of nature or local culture c) Making frames painting from bamboo d) Installation of frames on painting works. The results of the training for a form of xhibition of works. The result of an artistic and cultural training effort (creation, appreciation of art) at the community level. The objects of the training are decorative, beautify the guest house room and mainly reveal the lontara script, the work of the originator of the lontara script, daeng pamatte.Keywords: Souvenir,specia lincreasing,family household,income